Transformasi Islamic Worldview dalam Pemikiran Islam di Dunia Barat - Widyaningsih, Erna; Mujahid, Kasori (Lembaga Yasin AlSys, 2025)
The transformation of the Islamic worldview in Islamic thought in the Western world reflects the dynamic interaction between Islamic traditions and the context of modernity and secularization. This study aims to analyze how the Islamic worldview undergoes transformation within the thoughts of Muslim intellectuals in the Western world. Using a qualitative approach based on literature review, this research identifies a paradigm shift from traditional understanding toward the integration of Islamic values into modern discourse. The findings reveal that this transformation involves not only value adaptation but also the recontextualization of Islamic principles to address philosophical, social, and epistemological challenges in the Western world. This transformation opens opportunities for a more harmonious synthesis between Islamic values and the Western context without losing its identity.